Hell and the Mercy of God - Reimers, Adrian J. (Book collections on Project MUSE., 2017)
If God is truly merciful and loving, perfect in goodness, how can he consign human beings created in his own image to eternal torment in hell? God's goodness seems incompatible with inflicting horrible evil upon those who oppose his will and defy his law. If to this paradox we add the metaphysical requirement that God be perfect in goodness, the eternal evil of hell seems to be contradictory to God's own nature. Catholic philosopher Adrian Reimers takes on these challenges inHell and the Mercy of God, drawing on relevant sources from Aristotle to Aquinas, from Dante to Tolkien, from Wagner to John Paul II, along with Billie Holliday, The Godfather, and the music of George Gershwin. He presents a philosophical theology, grounded in Scripture, of the nature of goodness and evil, exploring various types of pain, the seven capital sins, the resurrection of the body, the meaning ofmammon, the core meaning of idolatry, the psychology of Satan and those who choose his path, and the moral responsibility of the human person. These reflections illuminate the intelligibility of orthodox Catholic teachings on the goodness of God and the reality of hell. Hell is not an arbitrary imposition set up for human rule-breakers but a continuation of a freely chosen way of life manifest even in this world. Examples from history, art, and contemporary culture lead the author to conclude that anyone who does not believe in the reality of hell is not paying enough attention. And yet, mercy and hope remain triumphant, because, just as Christ offƯers entrance into paradise to the "good thief" Dismas on the cross, God continues to oƯffer repentance and salvation to all who live.